Hospital Volume and Other Risk Factors for In-Hospital Mortality among Diverticulitis Patients: A Nationwide Analysis. Issue 4 (2015) - Diamant, Michael J; Coward, Stephanie; Buie, W Donald; MacLean, Anthony; Dixon, Elijah; Ball, Chad G; Schaffer, Samuel; Kaplan, Gilaad G
Abstract : BACKGROUND: Previous studies have found that a higher volume of colorectal surgery was associated with lower mortality rates. While diverticulitis is an increasingly common condition, the effect of hospital volume on outcomes among diverticulitis patients is unknown. OBJECTIVE: To evaluate the relationship between hospital volume and other factors on in-hospital mortality among patients admitted for diverticulitis. METHODS: Data from the Nationwide Inpatient Sample (years 1993 to 2008) were analyzed to identify 822, 865 patients representing 4, 108, 726 admissions for diverticulitis. Hospitals were divided into quartiles based on the volume of diverticulitis cases admitted over the study period, adjusted for years contributed to the dataset. Mortality according to hospital volume was modelled using logistic regression adjusting for age, sex, race, comorbidities, health care insurance, admission type, calendar year, colectomy, disease severity and clustering. Risk estimates were expressed as adjusted ORs with 95% CIs. RESULTS: Patients at high-volume hospitals were more likely to be admitted emergently, undergo surgical treatment and have more severe disease. In-hospital mortality was higher among the lowest quartile of hospital volume compared with the highest volume (OR 1.13 [95% CI 1.05 to 1.21]). In-hospital mortality was increased among patients admitted emergently (OR 2.58 [95% CI 2.40 to 2.78]) as well as those receiving surgical treatment (OR 3.60 [95% CI 3.42 to 3.78]). CONCLUSIONS: Diverticulitis patients admitted to hospitals with a low volume of diverticulitis cases had an increased risk for death compared with those admitted to high-volume centres.